Hubungan Status Gizi, Tingkat Stress Dengan Siklus Menstruasi Pada Siswi Madrasah Tsanawiyah (Mts) Negeri 2 Tanggamus Tahun 2024 - Meliana Meliana; Abdullah Abdullah; Alifiyanti Muharramah; Mayesti Akhriani (Departement of Mathematics Education, 2024)
The menstrual cycle in adolescent girls or women ranges from 21 up to 35 days, with 10 up to 15% having a menstrual cycle of 28 days and a menstrual duration of 3 up to 5 days. However, some also last 7 to 8 days, depending on each individual. Irregular menstrual cycles can have an impact on fertility and reproductive disorders and can make it difficult to get pregnant because ovulation does not occur. The research objective was to determine the correlation between nutritional status, stress levels and the menstrual cycle in female students of Islamic Schooling of Madrasah Tsanawiyah State 2 Tanggamus 2024. Data collection was carried out using analytical survey analysis with a cross-sectional design. The population of this research was 328 class VII and class VIII female students, with a sample of 90 female students. Data analysis used the Chi-square statistical test and gamma test. After conducting statistical tests using the gamma test, a p-value of 0.044 was obtained, meaning Ha was accepted and Ho was rejected. This shows there was a correlation between nutritional status and the menstrual cycle in female students of Madrasah Tsanawiyah (MTs) State 2 Tanggamus in 2024. On the other hand, the results of statistical tests using the chi-square test show a p-value of 0.725, which means Ho is accepted and Ha is rejected. In other words, there is no correlation between stress levels and the menstrual cycle of female students at Madrasah Tsanawiyah (MTS) State 2 Tanggamus in 2024. It was concluded that there was a correlation between nutritional status and the menstrual cycle in female students of Madrasah Tsanawiyah (MTs) State 2 Tanggamus in 2024, there was no correlation between stress levels and the menstrual cycle in female students of Madrasah Tsanawiyah (MTs) State 2 Tanggamus in 2024.